Introduction to the humanities : visual and performing arts - Marcos, Lucivilla L. (Makati City, Philippines : Mindshapers Co. Inc., 2006)
This workbook- textbook " Introduction to the Humanities" has been prepared to focus on the Visual Arts, Painting, Sculpture, Architecture; the Performing Arts -- Music, Dance and Drama. With proper motivation and guidance from the teachers, the students are expected to present to the class their own artistic works as output of their study of each particular art. At the end of every chapter are exercise to measure what the students have learned as well as to challenge their creativity. - - Preface
Chapter I. Humanities: Meaning, Significance and Components -- Chapter II. Painting -- Chapter III. Sculpture -- Chapter IV. Architecture -- Chapter V. Music -- Chapter VI. Drama -- Chapter VII. Dance.
Includes bibliographical references.
Keywords: HUMANITIES